APPLICATION OF A SCIENTIFIC APPROACH TO SCIENCE LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS. - Oktaviani, Aulia Putri; Albina D, Cintia Putrie; Rahmah, Wafa Novia; Agna, Siti Mulia (Prodi Pendidikan IPS, Universitas Tanjungpura, 2024)
This article explains social studies learning strategies that use a scientific approach to improve student quality. The problem formulation in this article is how to introduce a scientific approach to social studies learning to improve students' critical thinking skills. The aim of this initiative is to improve students' abilities as learners who are able to think critically and solve social problems. The method used is descriptive quantitative with a library study approach, data collection through source search and compilation from various sources such as journals and existing research. The analysis method uses descriptive analysis. Various library material references are analyzed in detail to support this idea. The results of this research show that a scientific approach must take five steps: 1) Observe. 2) Questioning 3) Associating. 4) Communicate and 5) Finish. By applying the steps of this scientific approach, students can develop a deep understanding in social studies learning and improve critical thinking skills, good communication skills, and an understanding of connecting with the real world